Repeat Ascaris challenge reduces worm intensity through gastric cellular reprograming. - Yifan Wu; Charlie Suarez-Reyes; Nina L Tang; Alexander R Kneubehl; Jill E Weatherhead (PLoS Neglected Tropical Diseases)
Ascariasis (roundworm) is the most prevalent parasitic nematode infection worldwide, impacting approximately 500 million people predominantly in low- and middle-income countries (LMICs). While people of all ages are infected with Ascaris, infection intensity (defined by worm burden) paradoxically peaks in pre-school and school-aged children but then declines with age. The cause of age-dependent Ascaris worm intensity is not well understood but may be dependent on cellular changes in mucosal barrier sites. We have previously found that the gastric mucosa is a critical barrier site for Ascaris infection as ingested Ascaris larvae use acidic mammalian chitinase (AMCase) secreted by gastric chief cells and acid secreted by gastric parietal cells to hatch. After hatching, larvae translocate across the gastric mucosa to initiate the larval migratory cycle. However, mucosal injury induced by administration of Tamoxifen results in cellular changes that impair Ascaris hatching and reduce larval translocation across the gastric mucosa. Since individuals in endemic settings often experience recurrent infection throughout their lives, we set out to determine how repeated Ascaris exposures affect the gastric mucosa and the intensity of resultant infections. In this study, we established a repeated Ascaris suum challenge mouse model and found that repeated Ascaris challenge caused cellular changes in the gastric mucosa which reduced worm intensity in the liver. Importantly, these decreases in infection intensity following repeated infections occurred independent of the adaptive immune response. These findings indicate that gastric cellular changes may be a key mechanism leading to the observed age-dependent Ascaris worm intensity changes from childhood to adulthood.